Community Education on Air Pollution–Related Skin Health Integrated with a Micellar Water Workshop in Jakarta - Laurensia; Yulius Evan Christian; Patrycia Setiawan; Vanessa Gracia Santoso; Venestrata Gracia; Felisca Emmalyn Alwi; Sharon Susanto (LP2M INSURI Ponorogo, 2026)
Jakarta is one of the most polluted cities in Indonesia, which often exceeds safe health standards. Despite growing evidence linking air pollution to dermatological conditions, public knowledge and preventive behavior in urban communities remain limited and poorly addressed in community health programs. The objective of this program is to increase community knowledge about the effects of air pollution on skin health through a community-based education model that integrates pre-test and post-test assessments with practical activities. The program was conducted in three phases: pre-implementation, including material preparation and pretest-posttest assessment design; implementation, including a health education session and a practical workshop on micellar water formulation; and post-implementation, through evaluation and reporting. The activity was held on October 15, 2025, with 30 participants. Results showed a statistically significant improvement in participant knowledge, as measured by a paired t-test (p<0,05), with average scores increasing from 53.0 to 65.67. The assessment was conducted using a 10-question questionnaire before and after the activity. This activity highlights the potential of integrated educational and practical approaches to improve community understanding of environmental health risks and support the adoption of preventive self-care practices.